A Comparative Study of the Oxidation and Wet Chemical Methods for Uncapping the Multi-Walled Carbon Nanotubes - M. Valinejad; A. Shokuhfar; B. Arab (Журнал нано- та електронної фізики)
Carbon nanotubes (CNTs) are generally capped at either end with a half of a fullerene. Hence, for storing different materials into the hollow space of CNTs, their caps need to be removed in the first step. In this study, we studied both the oxidation and wet chemical (acid-based) methods for opening the multi-walled carbon nanotubes (MWCNTs). In The oxidation method, 250 mg of CNTs were heated at 810 °C for 15 minutes in the air, and yielded about 56 % opened CNTs, while 78 % weight loss was recorded. The second sample with the same weight of the sample 1 was treated at 780 °C for 15 min. The weight loss and yielded uncapped CNTs were recorded 36 % and 47 %, respectively. The 780 °C was observed to be more appropriate than the higher temperature. In the acid-based method, the CNTs were refluxed in boiling nitric acid (65 % analar grade) at 110 °C for 12 h. In this case, about 80 % of the CNTs were thoroughly opened without any weight loss. The acid-based method was finally deduced to be more economical and efficient than the oxidation method.